Determination of Gossypol Content in Cottonseed Oil and Cake by HPLC and GC/ms - EL-Hassan, Ayia M.; M. Nour, Salah; O.Babiker, mohammed (Gezira Journal of Engineering and Applied Sciences; مجلد 15 عدد 1 (2020), 2021)
This study investigated gossypol content in cottonseed oil and cottonseed cake of Bt cottonseed (Seeni1) and non-Bt cottonseed (Barakat 90, Abdeen, Mixed) in oil and cake by difference methods. Among the all non-Bt cottonseed varieties Barakat (90) had shown higher amount of gossypol content in oil and cake (470 and 467) ppm (890 and 897) ppm by using HPLC and GC/MS respectively. Moreover, Bt cottonseed variety (Seeni1) had shown lower amount of gossypol content using both methods (320 and 326) ppm and (640 and 635) ppm by using HPLC and GC/MS respectively. From the present study, we observed that was no significant difference in gossypol content between Bt cottonseed and non-Bt cottonseed varieties. Bt cottonseed variety has lower amount of gossypol being of more economical importance to farmers having cotton as their cash crop.